“I translate the school language”: education in the shadows and the educational practices of tutors in traditional Brazilian communities - Ribeiro Costa da Cunha Ferreira, Raquel; Vianna Ferreira, Arthur (Aprender, 2025)
The article aims to understand the educational practices of tutors who work in two fishing communities located on the banks of Guanabara Bay, in the state of Rio de Janeiro, Brazil. The tutors are teaching professionals, generally women, who work in peripheral communities, teaching students with difficulties, who are organized into small groups. The theoretical support is based on Social Pedagogy, from the perspective of Hospitality Pedagogy, by Isabel Baptista, and on the Theory of Social Representations, in the societal approach, by Willem Doise, focusing on the first stage of his three-dimensional model, common beliefs. The methodology is based on the rhetorical-philosophical analysis of the speeches obtained from semi-structured interviews carried out with the participants, totaling 07. We can point out from the data obtained from the research that the explainers have common beliefs that their activity is different from that existing in the official education system, as they are able to translate the school’s language for the students, being recognized by the communities in which they work. We also observe the presence of otherness and social ties in the educational practices developed by the tutors, who consider the student in their individuality, welcoming them and respecting, in an ethical way, their life history and their insertion in the community space.